Hepatoprotective Effect of Moringa Oleifera Leaves Extract on Acetaminophen-Induced Liver Damage in Rats - Linggi Gaundar, Uma Nanthini (2007)
Moringa oleifera (MO) is reported to have various medicinal properties. The aim of this study is to evaluate the hepatoprotective effect of MO leaf extract against acetaminophen (APAP) induced liver damage in rats. A dose of 3g/kg APAP was selected to induce liver damage. Seventy male Sprague-Dawley rats (n=70) were divided into seven groups. Five groups of animals were given various oral pretreatments of 200mg/kg MO, 800mg/kg MO and 200mg/kg Silymarin (Sil) in distilled water at 3ml/day for fourteen days. Meanwhile, two groups served as hepatotoxicity (3g/kgAPAP) and vehicle (40% sucrose) control groups were given distilled water in the similar manner. On day 15, the animals were challenged with 3g/kg APAP in 40% sucrose except for rats in the vehicle (40% sucrose) and MO control groups which received 40% sucrose solution. After 24 and 48 hours blood was withdrawn and livers were harvested. Plasma was prepared and liver function was carried out to determine levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP). Liver samples were taken for histopathalogical examination, measurement of hepatic reduced glutathione (GSH) content, glutathione-S-transferase (GST), glutathione peroxidase (GPx) and glutathione reductase (GR) activities as well as determining malondialdehyde (MDA) levels. Statistical analysis was performed using analysis of variance (ANOVA) and Kruskall Wallis analysis of variance coupled with the Mann–Whitney U-test. APAP treatment caused significant elevation (p<0.05) of ALT, AST after 24 and 48 hours. Histopathological observations substantiated these findings showing significant (p<0.05) liver damage. APAP treatment caused marked reduction (p<0.05) in hepitic GSH content, GST and GPx. activities coupled with significant increase (p< 0.05) in lipid peroxidation index. The changes observed were time dependent with more changes were noted after 48 hours. Significant (p<0.05) elevation of ALP and significant (p<0.05) decline of GR activity was only noted after 48 hours compared to other groups. 200mg/kg and 800mg/kg MO extract equally showed a significant (p<0.05) amelioration of ALT, AST and ALP levels and a significant reduction (p<0.05) of pathological alteration in a manner similar to Sil. MO extracts showed no signs of toxicity up to a dose level of 800 mg/kg. MO alone significantly increased (p<0.05) GSH content and restored GSH level (p<0.05) in the groups given MO and challenged with APAP. MO alone showed insignificant increase of GST, Gap and GR activities. The significant increase (p<0.05) of these antioxidant enzymes observed in groups received MO extracts and challenged with APAP. Lipid peroxidation was significantly (p<0.05) inhibited by the extracts in dose independent manner. A significant (p<0.05) increase of GST activities by 200mg/kg and 800mg/kg MO extracts to the level higher than vehicle group were observed as early as 24 hours in comparison with rats given pretreatment of Silymarin. On the other hand, 200 mg/kg MO significantly (p<0.05) showed similar increase in GPx activity to the level higher than vehicle group in comparison with groups that given 200mg/kg Sil and 800mg/kg MO pretreatment. Prevention of enzyme leakage, preservation of hepatocytes structural integrity, prevention of GSH depletion, restoration of antioxidant enzymes activity that is essential in accelerating detoxification and excretion of APAP toxic metabolites, as well inhibition of lipid peroxidative processes reveals that the extracts of MO leaves possesses potential hepatoprotective activity against APAP induced damage in rats.